2017
DOI: 10.1016/j.bjps.2017.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Determining the outcomes of post-mastectomy radiation therapy delivered to the definitive implant in patients undergoing one- and two-stage implant-based breast reconstruction: A systematic review and meta-analysis

Abstract: This meta-analysis demonstrates that within the first 5 years, post implant-based reconstruction for those patients who receive PMRT, the rates of adverse events are increased, and there is a significant reduction in patient satisfaction and cosmetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 21 publications
0
47
0
1
Order By: Relevance
“…16,18 Additional studies have demonstrated increased rates of capsular contracture, tissue infection, and extrusion of implants in patients who received postmastectomy radiotherapy. 16,[19][20][21][22] Notably, several authors have suggested that autologous tissue reconstruction is preferable to implant-based reconstruction in the setting of radiation. 15,[23][24][25][26][27] Given that the safety profile and optimal timing of radiation in the setting of breast reconstruction remains controversial, 8,11,[28][29][30] should radiation patterns change, the rates of complications with implant-based reconstruction in the setting of radiation may also change.…”
Section: Discussionmentioning
confidence: 99%
“…16,18 Additional studies have demonstrated increased rates of capsular contracture, tissue infection, and extrusion of implants in patients who received postmastectomy radiotherapy. 16,[19][20][21][22] Notably, several authors have suggested that autologous tissue reconstruction is preferable to implant-based reconstruction in the setting of radiation. 15,[23][24][25][26][27] Given that the safety profile and optimal timing of radiation in the setting of breast reconstruction remains controversial, 8,11,[28][29][30] should radiation patterns change, the rates of complications with implant-based reconstruction in the setting of radiation may also change.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients who have undergone PMRT, immediate reconstruction surgery should be avoided because it increases the rates of complications and implant loss, especially in the context of implant-based breast reconstruction. It also leads to a significant reduction in patient satisfaction and worse cosmetic outcome [11]. Hence, from this point of view, we think that it is preferable to .…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol regarding SLNs and non-SLNs were described in detail in our previous study [11]. Hence, we briefly describe our approach below.…”
Section: Methodsmentioning
confidence: 99%
“…The generic reference to ‘breast reconstruction’ was intended to capture all articles addressing the type and timing of breast reconstruction. Two authors independently reviewed abstracts of all studies published between 1985 and 2014, and the full texts of those studies published in 2015–2017. Levels of clinical evidence (LoE) were evaluated for each publication and scored from I to V by employing Oxford criteria.…”
Section: Methodsmentioning
confidence: 99%